RF stability performance of SOI junctionless FinFET and impact of process variation. (January 2017) - Jegadheesan, V.; Sivasankaran, K.
Abstract: In this paper we investigate the impact of process parameter variations such as temperature (T), channel doping concentration (ND ), Fin height (Hfin ) and Fin width (Wfin ) on Radio Frequency (RF) stability performance of 20 nm Silicon on Insulator Junctionless FinFET (SOI JLFinFET). The developed RF stability model provides relation between critical frequency (fk ) and small signal parameters which can be optimized for improved stability. Results shows as temperature increases (27–200 °C) cutoff frequency (fT ) and maximum oscillation frequency (fmax ) reduced by 12% and 8% respectively also stability factor (K) decreases by 20% at high frequency. Increasing ND, Hfin and Wfin increases fT and fmax but degrades stability performance. The result also provides optimized design guideline for operating SOI JLFinFET under RF range.